2018
DOI: 10.3390/nano8110942
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Phase Exfoliation of Graphene: An Overview on Exfoliation Media, Techniques, and Challenges

Abstract: Graphene, a two-dimensional (2D) carbon nanomaterial, has attracted worldwide attention owing to its fascinating properties. One of critical bottlenecks on some important classes of applications, such as printed electronics, conductive coatings, and composite fillers, is the lack of industrial-scale methods to produce high-quality graphene in the form of liquid suspensions, inks, or dispersions. Since 2008, when liquid-phase exfoliation (LPE) of graphene via sonication was initiated, huge progress has been mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
221
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(234 citation statements)
references
References 131 publications
2
221
1
10
Order By: Relevance
“…Thus it is anticipated that it cannot full the requirements for commercial consumption of elevated-quality graphene. 15,16,17 Additionally, the pseudo-spin symmetry is conserved in this case due to the lack of defects/vacancies and adatoms, which is a major problem for memory devices and spin-based devices. Tucek et al have shown that the controlled sp 3 functionalization of graphene to make zig-zag conjugated sp 2 carbon chains can provide a suitable matrix for strong ferromagnetic ordering up to room temperature.…”
Section: Nanoscale Advances Reviewmentioning
confidence: 99%
“…Thus it is anticipated that it cannot full the requirements for commercial consumption of elevated-quality graphene. 15,16,17 Additionally, the pseudo-spin symmetry is conserved in this case due to the lack of defects/vacancies and adatoms, which is a major problem for memory devices and spin-based devices. Tucek et al have shown that the controlled sp 3 functionalization of graphene to make zig-zag conjugated sp 2 carbon chains can provide a suitable matrix for strong ferromagnetic ordering up to room temperature.…”
Section: Nanoscale Advances Reviewmentioning
confidence: 99%
“…This method uses intercalation and heating methods. Intercalation is a method of changing the distance between the atomic bonds in a crystal layer [14], while heating is a method that serves to break the bonds between atoms in the crystal. Graphite is composed of graphene layers having van der Waals bonds between adjancent layers and covalent bonds between carbon atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The LPE using ultrasonication produces effective exfoliation method and has the potential to produce monolayer or few-layer graphene at relatively high concentration. Typically, the power of sonication is used to induce physical or chemical changes in some systems through the generation of cavitation bubbles [14].…”
Section: Introductionmentioning
confidence: 99%
“…Both GO and rGO obtained are amorphous materials carrying structural defects and residual OCGs . Another way to exfoliate graphite would be to proceed to liquid phase exfoliation (LPE), which involves high‐shear mixing or sonication process in suitable stabilizing solutions containing dispersants such as organic solvents, surfactant and ionic liquids . While low efficiencies were mostly achieved with sonication assisted LPE, the use of shear force for exfoliation is giving more promising results .…”
Section: Graphene Nomenclature and Synthesismentioning
confidence: 99%